Achieving net zero emissions in India’s power sector: the dilemma between climate justice and energy justice - Kopal Dhandhania; Shivika Mittal; Minal Pathak (Energy and Climate Change, 2026)

Mind the gap: evaluating implementation of urban climate plans in three Indian cities - Minal Pathak; Shaurya Patel; Nupur Joshi (Sustainability Science, 2026)

Climate-driven transformations: A framework for the sustainable urban landscape system to enhance heat resilience - Boze Huang; Jinda Qi; Minal Pathak; Ayyoob Sharifi; Ali Cheshmehzangi; Shady Attia; Andreas Matzarakis; Amirhosein Ghaffarianhoseini; Geun Young Yun; Amos Darko; Xiao Liu; Bao-Jie He (Sustainable Cities and Society, 2025)

Recognizing historic injustice in a coal-rich district: A case study of Singrauli, India - Kopal Dhandhania; Jeemol Unni; Minal Pathak (Resources Policy, 2025)

Editorial: One climate, one urban, one health - Guangtao Fan; Yichen Yu; Meng Gao; Ayyoob Sharifi; Minal Pathak; Kai Zhang; Pablo Fernández de Arróyabe Hernáez; Qihong Deng (Sustainable Cities and Society, 2025)

Beyond synergies: understanding SDG trade-offs, equity and implementation challenges of sectoral climate change mitigation options - Kirsten Halsnæs; Shreya Some; Minal Pathak (Sustainability Science, 2024)
Mitigation actions needed to achieve the ambitions of the Paris agreement to limit global temperature rise to 1.5 °C or below 2 °C have to align with sustainable development. In the near term, this implies a better understanding of context-specific challenges in integrating sustainability with climate policies during the designing, planning, implementation and financing stages. Through a review of selected studies across regions, this paper draws out conclusions focussing on mitigation–sustainable development goal (SDG) trade-offs, with implications on costs and equity for different development contexts. Studies show that trade-offs depend on how the option is implemented and at what scale; mitigation options such as afforestation, biomass production and digitalisation are examples of this. Some options could also result in significant adverse environmental impacts as in the case of battery waste and raw material resources for electric vehicle (EV) or air pollution associated with compact urban development. We find the most important factors influencing equity include unequal access (e.g. urban green spaces and public transportation), high costs (e.g. EV) and financial constraints. Major knowledge gaps include (i) limited empirical evidence of SDG-related trade-offs associated with scaling up mitigation options, (ii) limited understanding of the extent to which benefits are experienced by different groups, (iii) an understanding of the extent to which local context was considered when assessing mitigation–SDG interaction, including the engagement of stakeholders and (iv) synergies and trade-offs associated with cross-sectoral policies. The paper recommends ex-post analysis of detailed and place-based cases that document how synergies and trade-offs emerged and how these were addressed.

Equity in climate scholarship: a manifesto for action - E. Lisa F. Schipper; Jonathan Ensor; Aditi Mukherji; Alisher Mirzabaev; Arabella Fraser; Blane Harvey; Edmond Totin; Matthias Garschagen; Minal Pathak; Philip Antwi-Agyei; Thomas Tanner; Zoha Shawoo (Climate and Development, 2021)

Communicating climate change findings from IPCC reports: insights from outreach events in India - Minal Pathak; Joyashree Roy; Shaurya Patel; Shreya Some; Purvi Vyas; Nandini Das; Priyadarshi Shukla (Climatic Change, 2021)
In recent years, the Intergovernmental Panel on Climate Change (IPCC) has been collaborating with Indian institutions to organise outreach events. This essay draws on the perspective of participants, speakers and organisers of 17 in-person outreach events conducted across India in 2018 and 2020, to share insights and recommendations for future IPCC events in India and other developing country contexts. The formats analysed in this essay range from panel events with very large public audiences to more focused workshops, meetings and seminars. Target audiences covered both academic and non-academic audiences and included researchers, teachers, students, industry and NGOs. The events, while achieving their main objective of communicating the findings of IPCC reports, also provided a platform for open discussion of localised climate impacts and good practices in adaptation and mitigation. There are, however, notable challenges to public outreach in India, specifically in terms of attracting an adequate number of participants, experts’ availability, communicating to a diverse audience and translation into local languages. The biggest challenge faced by speakers was a lack of knowledge about the number of attendees and the composition of the audience prior to an event. It is our recommendation that future outreach events in India are designed to be interactive, tailored to the regional context and complemented by simplified communication materials. Speakers should be provided with audience information and background prior to the event, and greater reach into rural areas, including school children, could be achieved with material in local languages. Additionally, event organisers often require logistical and operational support to host outreach events.